A Threshold Model of Urban Development - Alberto Vesperoni; Paul Schweinzer (Center for Economic Studies and ifo Institute (CESifo), 2018)
We propose a simple model of distribution of economic activity across cities of endogenous size and number determined by individual incentives in the tradition of threshold models of social interaction. The individuals populating our model are endowed with idiosyncratic entrepreneurial creativity the realization of which requires urban agglomeration linked to a crowding cost. As the latter is higher in cities of larger size, this leads to a trade-off between productivity and congestion. While our focus on distributive aspects comes at the cost of highly stylized behavior, we aim to provide a tractable framework to think about the interlinkages between various measures of urban development which became increasingly available through accessible data sets. Our predictions include an U-shaped relationship between the well-known measures of urbanization and urban primacy, a hypothesis that we test empirically using World Bank data.
Keywords: C70; D71; O18; Q56; 330; agglomeration; urbanization; development